Fluidization Analysis of Thickening in the Deep Cone for Cemented Paste Backfill - Haiyong Cheng; Jin Liu; Shunchuan Wu; Xiaoqiang Zhang (Advances in Materials Science and Engineering)
Cemented paste backfill (CPB) can effectively eliminate the risk of dam break in goaf and tailings pond which used tailings waste. Deep cone thickener (DCT) is an efficient machine for the system of paste preparation, and the concentration of slurry at the bottom is high and distributed unevenly, which will cause too much partial resistance and failure of thickener. Focusing on the above problems, fluidization design was conducted by using the fluidization theory. The delivery law of flocs was analyzed, and the isobaric surface was obtained. The equation of pressure and critical velocity of the ideal fluidized bed was acquired by analyzing the relationship between pressure and critical velocity. Based on the characteristics of tailings and distribution of the bonding zone, the arrangement, number, and working mode of spray nozzles were reformed. It is verified that the failure time of thickener decreased from 14 hours to 1 hour and the range of concentration increased from 74%∼78% to 78%∼80%, which improved the stability and reliability of DCT. The depth thickening mechanism is obtained, and the thickening method has been improved which provides a theoretical basis for the effective preparation of paste.